Etika Profesi Hakim dalam Melaksanakan Tugas dan Tanggung Jawab dalam Penegakan Hukum - Muhammad Rafli; Kayus Kayowuan L. (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Code of Ethics becomes an ethical principle in the profession of a judge which becomes the basis for every decision making by a judge as a law enforcement officer, as well as how the challenges and dilemmas faced by a judge in its in-depth implementation. The aims and objectives of this research aim to provide an understanding to the public regarding the guidelines and obstacles for a judge in carrying out this research is a normative juridical research, namely legal research conducted by examining library materials or secondary data only. The approach used in this research is the statute approach, which is an approach carried out by examining all laws and regulations related to the legal issues being discussed (studied) and the case approach. The code of ethics of a judge has been regulated in the Joint Decree of the Chairman of the Supreme Court of the Republic of Indonesia and the Chairman of the Judicial Commission of the Republic of Indonesia Number 047/KMA/SKB/IV/2009 02/SKB/P.KY/IV/2009 concerning the Code of Ethics and Code of Conduct for Judges. However, a judge in his role as a legal defender is often faced with various ethical dilemmas in making legal decisions. These dilemmas can affect the decision-making process and the final outcome of a case. A judge as a legal defender is often faced with various ethical dilemmas in making decisions that finalise the outcome. There are ethical dilemmas that are often faced by judges in carrying out their duties as law enforcers. Judges are often faced with situations where the strict application of the law is not always in line with the principles of justice. This helps prevent arbitrary action and ensures that the law is applied consistently.